Erased by the Plough, Spotted from the Air. Remains of Earthwork Sites from Silesia - Furmanek, Mirosław; Wroniecki, Piotr (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2017)
Since 2012 south-western Poland has been subject to regular aerial prospection campaigns that covered a vast area of the Upper Silesian, Lower Silesian and Opole regions. Eight surveys were conducted in with a total of 44 flight hours during late spring and summer dates. Their primary aim was the recognition of Neolithic and Early Bronze Age communities and landscapes. Additional photographic documentation of known and newly discovered features from other chronological periods was also obtained. The article presents a selection of data from five medieval settlements (Borucin site 2, Chrzelice site 1, Gniechowice site 1, Komorno site 1, Stary Zamek site 6), whose common feature is their nearly completely leveled earthworks, which makes the presented aerial imagery a basic source of information about them. The potential of remote sensing approaches in the case of quickly deteriorating archeological terrain forms, although not used frequently, has numerous advantages especially in contrary to the still favoured destructive excavation strategies. A visible intensification of archeological site destruction due to all-round development of urban and rural areas has affected all types of archeological sites – also those characterized (until relatively recently) by unique and complex earthwork remains. This situation requires an adaptation of new protection strategies, as well as alternative cognitive and methodical schemes. The case studies presented in this paper are a final wakeup call showcasing the scale of the ongoing, countrywide, systematic destruction of important yet unknown or poorly researched archeological sites. The remedy in our opinion is the recognition of non-invasive remote sensing and geophysical techniques as primary research methods as they allow defining crucial elements, such as form, size, layout, or functional interpretation.
Keywords: aerial prospection; remote sensing; fortified settlements; Silesia; Medieval